Transformation of Multimedia Journalism Learning Practices in The Era of Social Media: The Influence of Instagram and TikTok on Gen Z Student in West Jakarta - Gurning, Sisca T. (Jurnal Komunikasi, 2024)
Rapidly developed digital media technology has made it easier for everyone to contribute to the world of journalism. Social media, such as Instagram and TikTok, have increased students' interest in journalism and provided opportunities for them to be part of news production. Higher education learning spaces will have to adapt to this development. This study aims to examine the influence of social media on learning multimedia journalism through social media for Gen Z students at a university in West Jakarta, in order to produce quality graduates who are able to adapt to the development of digital technology. Research methodology with quantitative approach with a sample of multimedia journalism students. Data analysis based on the reliability testing method used in this study is Cronbach's Alpha. Validity testing using the SPSS program with the Pearson Correlation Method, which correlates each item with the total score of the questionnaire items. The results indicated that social media influenced multimedia journalism learning practices, which were also determined by other factors.